Dinâmica temporal do estado fisiológico de cana-de-açúcar sob déficit hídrico - Garcia, Fernando Henrique Silva (2015)
In Brazil, sugarcane is the main agricultural crop for clean power generation, provided by its high biomass production in the field, associated with positive energy balance for biofuel production. However, in recent years, sugarcane cultivation suffered significant reduction in production due to frequent periods of dry spells over the years. Thus, the period of time of sugarcane exposure to drought could cause changes in the physiological mechanisms in order to minimize the negative effects of successive periods of water restriction. The aim of this study was to evaluate the temporal dynamics of physiological state of four varieties of sugarcane under drought. The experiment was conducted at the Universidade Federal de Lavras, with the sugarcane varieties: RB867515 and RB835486 (tolerant) and RB 72454 and RB 855453 (susceptible), submitted to two cycles of drought and rehydration. Were analyzed the physiological variables: maximum and minimum water potential, photosynthesis rate, stomatal conductance, transpiration, respiration rate, chlorophyll concentration, relative water content and concentration of sucrose, starch and reducing sugar in the leaf. Data were submitted to principal component analysis. It was observed that the varieties of sugarcane showed decreases in all physiological variables analyzed after exposure to the first water deficit cycle. However, in the second exposure to drought, the varieties showed plasticity, for a smaller difference in physiological parameters to control compared to the first water deficit cycle. It was observed in this work that photosynthetic parameters can be modulators of changing physiological states of the front plants to water deficit.